ETHNIC MIGRANT ENTREPRENEURS’ OPPORTUNITY EXPLOITATION AND CULTURAL DISTANCE: A CLASSIFICATION THROUGH A MATRIX OF OPPORTUNITIES - Hamizah Abd Hamid; André M. Everett; Conor O’Kane (Asian Academy of Management Journal, 2018)
This research explores how ethnic migrant entrepreneurs (EMEs) from countries with a range of cultural differences to the host country exploit entrepreneurial opportunities in a single host country. Specifically, this study investigates: (1) the types of opportunities exploited by EMEs, and (2) the way they exploit these entrepreneurial opportunities. This study offers a contextualised insight on the link between entrepreneurial opportunity exploitation and cultural differences (operationalised using cultural distance, or CD). In particular, through highlighting the moderating role of CD, this study has developed a matrix of entrepreneurial opportunities based on cultural differences for EMEs, which can be useful for both EMEs and the host country’s administrative agencies. By accounting for culture in articulating the findings, this research contributes to theory by bridging the institutional-individual divide in entrepreneurship discussion through an institutional lens. A practical implication of this study is a delineation of opportunities according to cultural differences, which is beneficial for entrepreneurs across borders.